Self Healing dalam Perspektif Al-Qur'an : Studi Qur'an Tematik - Putri Hudani Nabila; Muhammad Alif (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to explore the concept of self-healing in the perspective of the Qur'an as a method of recovery and maintenance of mental health. The research uses a qualitative approach with a library research method with primary sources of the Qur'an and secondary sources in the form of books of interpretation, psychological literature, and Islamic books. The analysis technique uses thematic content analysis with the maudhū'ī interpretation method to collect and analyze verses related to self-healing values such as patience, dhikr, tawakkul, prayer, and gratitude with a contextual and psychological approach. The results show that mental health disorders according to the Qur'an can be caused by life tests and despicable traits such as despair, pride, spite, anger, prejudice, and anxiety, which result in mental unrest if not resolved. The Qur'an provides self-healing methods through the values of forgiveness, gratitude, patience, prayer, remembrance, and muhasabah, which are psychologically proven to help individuals calm the soul, control emotions, increase self-resilience, and strengthen faith in facing life's tests. Thus, Qur'an-based self-healing makes a significant contribution to mental health recovery, making individuals wiser, stronger, and having peace and cleanliness of heart in living life.